Clima organizacional y desempeño laboral de los servidores de las Unidades de Control Migratorio y Servicio de Apoyo Migratorio Loja y Zamora Chinchipe - Pinto Pinto, Paulina Dolores (2023)
This investigation was done in Migratory Control and Migratory Support Services Unities from Loja and Zamora Chinchipe, whose objective is to determine the organizational environment of public servers and its dimensions: place of work, motivation and evaluation, also processes compliance and objectives accomplished in work performance. Studies from different authors about organizational environment and work performance, and from scientific database as Scielo, Scholar Google, Dialnet, were taken in order to get information about portrayed variables. The methodology applied in this investigation is explanatory and correlational, whose main objective is to determine the relation between two concepts (variables) in this particular case. A survey was applied to 18 public servers, with a questionnaire of 25 items, structured by Likert scale, about organizational environment, which has 3 dimensions and 15 subdimensions. And a questionnaire about working performance, which has 2 dimensions and 10 subdimensions, which measures the grade or intensity of organizational environment and the level of working performance. The structure and the data analysis were done with the measurement and interpretation of the results obtained by the application of the survey and the elaboration of statistic graphics, where the different questions are shown with its answers. The results of the investigation showed that the organizational environment affects directly in working performance. Also, there are dimensions in the environment variable that have a statistically significative relation with working performance variables, resulting a tight relation between these two variables. Keywords: organizational environment, working performance, public servers, motivation, evaluation